Analisis Proses Pengajuan Klaim Nilai Tunai Penuh Melalui Sistem Asuransi Syariah pada PT Asuransi Jiwa Syariah Bumiputera Cabang Medan - Sri Aderafika Sani; Yusrizal Yusrizal (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
PT Asuransi Jiwa Syariah Bumiputera is one of the companies engaged in insurance by adhering to sharia principles. Claiming is the process of asking for guarantees or rights for losses suffered by the insured to the insurance company. This reseaarch is a research wiith qualitative method. The purposse of thiis study is to explaine how the procedure for submitting Full Cash Value at PT Asuransi Jiwa Syariah Bumiputera Medan Branch. From the result’s of the study, it is known thaat the procedure for submitting Full Cash Value at PT Asuransi Jiwa Syariah Bumiputera is quite simple, if the customer who submits a claim has submitted a complete claim application and submitted the documents required by PT Asuransi Jiwa Syariah Bumiputera, the claim will be approved. PT Asuransi Jiwa Syariah Bumiputera Medan Branc already has an informatiion system to manages data and transaction for submitting existing Full Cash Value Claims. However, the implementation is efficient, because there are still submissions made manually and using the media. Keywords: Application Process, Claim, Insurance